ANALISIS KELELAHAN KERJA DI PT MARUWA INDONESIA - Kurniawan, Ilham; Sirait, Ganda (Computer Science and Industrial Engineering, 2021)
Work fatigue is one of the occupational health and safety problems that can be a risk factor for accidents at work. Fatigue can be caused by several factors, both internal and external factors. The purpose of this study is to determine the level of fatigue and the factors that affect worker fatigue. This study uses mental workload analysis methods with the NASA TLX assessment questionnaire, and work fatigue with the Subjective Self Rating Test questionnaire from the Industrial Fatigue Research Committee (IFRC). The population in this study were 18 people. Sampling in this study was carried out by saturated sampling. Primary data collection using a questionnaire and secondary. The data processing technique used data analysis techniques, namely the chi-square test and correlation. Based on the results of research conducted, it was found that the score of work fatigue was 47.17. The score is classified as a high level of fatigue. This means that immediate action is needed to fix it in order to reduce the level of work fatigue which will have an impact on work accidents